(untitled) (HEALTH CARE: JURNAL KESEHATAN, 2024)
Market sanitation is an important aspect to achieve a healthy market. Market sanitation is a control measure that involves monitoring and assessing market effects, and is linked to disease development. Further research is needed because the initial observation results were not in accordance with Permenkes No.17 of 2020.The purpose of this study was to analyze the implementation of environmental hygiene and sanitation at PTM Square Lahat Market. This research is a descriptive study using a qualitative approach. This research was conducted by observation, interviews and documentation. Informants of this study as many as 9 people.The results showed that the PTM Square Lahat is clean water facilities are not regularly monitored or measured for water quality. Waste management facilities that are not separated between organic and inorganic. Drainage facilities that are not completely covered with metal grilles and are not smooth. Vector control facilities have never been sprayed every month. Toilet facilities are not separated for men and women. There are no handwashing facilities available with soap and running water. The application of personal hygiene for traders and buyers is not in accordance with the requirements, such as incomplete PPE and not washing hands.The conclusion of this study is that the implementation of hygiene and sanitation in the PTM Square Lahat Market is still not in accordance with the requirements of a healthy market. Suggestions for this research are to implement hygiene and sanitation in the market as well as monitoring and counseling by sanitarians and market managers to improve the quality of hygiene and sanitation in the market environment.